2022
DOI: 10.1111/cge.14282
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for activity analysis of single nucleotide polymorphisms associated with human diseases

Abstract: Genome-wide association studies (GWAS) have identified a large number of single nucleotide polymorphism (SNP) sites associated with human diseases. In the annotation of human diseases, especially cancers, SNPs, as an important component of genetic factors, have gained increasing attention. Given that most of the SNPs are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 117 publications
(210 reference statements)
0
3
0
Order By: Relevance
“…In the introduction, we discussed the advantages of using SNPs as IVs for MR. On the one hand, SNPs exist before acquired exposure, ensuring that causal estimations are unaffected by reverse causality. Furthermore, SNPs are inherited separately from other features and are unaffected by other confounding variables [ 14 ]. As a result, we used the most recent and comprehensive population genetic variation data from publicly accessible sources for MR analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the introduction, we discussed the advantages of using SNPs as IVs for MR. On the one hand, SNPs exist before acquired exposure, ensuring that causal estimations are unaffected by reverse causality. Furthermore, SNPs are inherited separately from other features and are unaffected by other confounding variables [ 14 ]. As a result, we used the most recent and comprehensive population genetic variation data from publicly accessible sources for MR analysis.…”
Section: Methodsmentioning
confidence: 99%
“…MR uses SNPs to infer causal relationships between exposures and outcomes. Its benefit is that SNPs exist before acquired exposure, and the correlation with the outcome follows a causal, temporal relationship and is unaffected by acquired environmental, social, and other confounding factors [ 14 ]. Independent sample MR, two-sample MR, multivariate MR, and bidirectional MR extensively investigate the causal association between risk factors and diseases [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the pathogenic effects of such molecular markers can be eliminated by changing lifestyle [48], breaking unhealthy habits [49], using low-molecular inhibitors of proteins encoded by the corresponding genes as medicines against excess of these proteins [50], using exogenous recombinant human proteins to compensate for the lack of these proteins caused by the corresponding SNPs [51] and using short antisense oligonucleotides as pharmacotherapy treatment of SNP-promoted misregulation of human gene expression [52]. That is why regulatory SNP markers are becoming more and more in focus as personalized medicine progresses [53].…”
Section: Introductionmentioning
confidence: 99%
“…A review reported that MIR215, MIR487A , and MIR502 are diagnostic and prognostic biomarkers in stable CAD [18]. SNPs are the most common type of genetic variation in human genomes which are mostly located in non-coding regions [19]. MiR-SNPs change the levels of miRNA expression, which increases one’s vulnerability to a number of diseases [20].…”
Section: Introductionmentioning
confidence: 99%